EVALUASI PERAN APARAT PENEGAKAN HUKUM DI INDONESIA - Ramlin Ahmad; Chaliza Yafirastiani Pangestu; Yossy Aulia Fadli (Universitas Kapuas, 2026)
This study analyzes the role of law enforcement officials in Indonesia in ensuring justice and legal certainty. It focuses on the effectiveness of law enforcement officials in addressing issues of corruption, drug abuse, and human rights violations. The methodology used is descriptive qualitative coupled with comparative analysis. Findings indicate structural challenges such as limited resources, integrity issues, and lack of coordination between institutions. Recommendations are provided for improving professionalism and reforming the law enforcement system.